2016
DOI: 10.1590/s1806-92902016000800003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of normal and PSE turkey breast meat for chemical composition, pH, color, myoglobin, and drip loss

Abstract: -The objective of this investigation was to determine the differences between normal and PSE (pale, soft, exudative) turkey breast meat in terms of chemical composition, pH, color, myoglobin, and drip loss. Pale and normal skinless, boneless turkey breast fillets were taken from a poultry slaughterhouse in Van/Turkey at about 2-3 h postmortem. Spectrocolorimetry (CIE L*a*b*), pH, protein, ash, dry matter, lipid, myoglobin, and drip loss were measured in normal and pale color turkey breast muscle. The normal br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
(26 reference statements)
0
5
1
Order By: Relevance
“…Consumers tend to be concerned about the colour of the meat as they consider it as an indicator of freshness ( Çelen et al., 2016 ; Fletcher, 2002 ; Kralik et al., 2018 ; Ribarski & Genchev, 2013 ). Despite the decreasing lightness values with increasing MNM, at 24 h post-slaughter, the L* values from both male and female breast meat reported in this study ranged from 45.72±1.49 to 49.17±4.53, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers tend to be concerned about the colour of the meat as they consider it as an indicator of freshness ( Çelen et al., 2016 ; Fletcher, 2002 ; Kralik et al., 2018 ; Ribarski & Genchev, 2013 ). Despite the decreasing lightness values with increasing MNM, at 24 h post-slaughter, the L* values from both male and female breast meat reported in this study ranged from 45.72±1.49 to 49.17±4.53, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Redness of the meat is a major determinant of acceptability of meat by consumers ( Mir et al., 2017 ). The content of myoglobin in muscle is the major factor impacting redness (a*) of the meat ( Çelen et al., 2016 ). Higher muscle myoglobin content is associated with increased redness and increased acceptability ( Neethling et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most serious defect of PSE meat is DL ( Çelen et al., 2016 ). Offer (1984) suggested that higher DL in chicken meat can be characterized by PSE meat and reduced DL by DFD.…”
Section: Resultsmentioning
confidence: 99%
“…The breast yield can vary between 22 and 30% and the yield of thighs with drumsticks can vary between 19 and 28% depending on the line, the slaughter age, and the sex. The range of ultimate pH comprises between 5.55 and 6.20 in breast muscle and between 5.75 and 6.30 in thigh muscle [3,4,5,9,16,17,18,19,20,21,22,23,24,25,26,27,28]. The juice loss can vary from 1 to 6% depending on the duration of cold storage and the cooking loss from 4% to 29% depending on the study and probably the cooking conditions and duration [7,8,9,10,12,14,15,19,23,25,28].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also reported the chemical composition of standard turkey meat. The water, protein, lipid, and ash contents of breast muscle vary between 72 and 75%, 21 and 28%, 0.4 and 4.0%, and 1.0 and 1.3%, respectively [3,5,7,9,10,12,14,15,16,20,24,26,27,28]. On the other hand, to our knowledge, no study has been published on the meat characteristics of male and female breeder turkeys.…”
Section: Introductionmentioning
confidence: 99%